Люминесцентные свойства люминофора YAG:Ce, BaF2 и керамики; Известия вузов. Физика; Т. 61, № 9-2 (729) - Степанов С. А. Сергей Александрович; Валиев Д. Т. Дамир Талгатович; Пайгин В. Д. Владимир Денисович; Шрайбер А. М. Анастасия Михайловна; Жвакина П. Д. Полина Дмитриевна; Ваганов В. А. Виталий Андреевич (2018, 2018)
Заглавие с экрана